Near-field Scattering of Light From a Hollow Particle With a Semisoft Boundary - Feinan Chen; Jia Li (IEEE Photonics Journal, 2016)
Within the validity of the first-order Born approximation, the near-field evanescent wave is analytically obtained from the scattering of a monochromatic plane wave from a spatially deterministic hollow particle with a semisoft boundary. The scattered spectral density shows the fluctuating profile in any cross-sectional plane. The increase of either the outer or the inner radius of the scattering potential accelerates the decay of the spectral density value. Given a smaller integer number in the summation index of the scattering potential, the scattered wave experiences less spreading in the near field. The obtained results have potential applications to generate the unique scattered patterns in the near field and the guidance of tiny particles along the desired trajectories.